2015
DOI: 10.1073/pnas.1422664112
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent regulation of microbial activity on sinking particles by polyunsaturated aldehydes: Implications for the carbon cycle

Abstract: Diatoms and other phytoplankton play a crucial role in the global carbon cycle, fixing CO 2 into organic carbon, which may then be exported to depth via sinking particles. The molecular diversity of this organic carbon is vast and many highly bioactive molecules have been identified. Polyunsaturated aldehydes (PUAs) are bioactive on various levels of the marine food web, and yet the potential for these molecules to affect the fate of organic carbon produced by diatoms remains an open question. In this study, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 55 publications
5
52
1
Order By: Relevance
“…It is possible that the responses we observed over longer timescales (i.e., 12-and 24-h) were influenced by community shifts, although we have no data that speaks to this directly. Edwards et al (2015) recently showed that additions of diatom-derived polyunsaturated aldehydes led to similar changes in enzyme activity after 24 h of incubation, but did not affect major shifts in community structure except at very high concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the responses we observed over longer timescales (i.e., 12-and 24-h) were influenced by community shifts, although we have no data that speaks to this directly. Edwards et al (2015) recently showed that additions of diatom-derived polyunsaturated aldehydes led to similar changes in enzyme activity after 24 h of incubation, but did not affect major shifts in community structure except at very high concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…of infochemicals on the activity of particle-associated bacterial assemblages, but they have thus far affirmed that bacterial signaling systems are involved in, and may either enhance or inhibit the rate of the degradation of sinking POC (Hmelo et al, 2011;Van Mooy et al, 2012;Edwards et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we hypothesize that particles have a stronger influence on particle‐attached than free‐living bacterial communities. However, very few studies have addressed the relationship between particle composition and microbes [ Edwards et al ., ]. The molecular characterization of particle‐attached microbiota and free‐living counterparts would help to reveal specific details about the mechanisms regulating fluxes of particulate organic carbon (POC) to DOC, which will ultimately influence the rates of carbon export and storage [ Jiao et al ., , ].…”
Section: Introductionmentioning
confidence: 99%
“…The sample preparation was modified according to former protocols (Wichard et al 2005b) to achieve a fast analytical workflow allowing cell enrichment, cell wounding, incubation for wound-activated PUA production, and removal of suspended cell material within 20 min before UHPLC-HRMS measurement. The novel analytical approach allows determining PUAs within the complex cell-free algal lysate matrix without work-and time-intensive derivatization procedures as introduced by d' Ippolito et al (2002a), Wichard et al (2005b), or Edwards et al (2015.…”
Section: Sample Preparationmentioning
confidence: 99%
“…This has been proven as a very robust and reliable method used by several laboratories (Taylor et al 2007;Morillo-Garcia et al 2014;Lavrentyev et al 2015). Derivatization is followed by extraction using hexane giving highly reproducible results in GC-MS. Alternatively, high performance liquid chromatography (HPLC)-separation of PUA-derived dinitrophenylhydrazones has been introduced on liquid-liquid extracts of PUAs (Edwards et al 2015). Recent studies focusing on oxylipin profiles of diatoms not only analyzed the volatile oxylipins using GC-MS but also screened for nonvolatile oxylipins such as fatty acid hydroperoxides, hydroxy-, epoxyhydroxy fatty acids or x-oxo-acids using liquid chromatography-mass spectrometry (LC-MS) (Barreiro et al 2011;Ianora et al 2015).…”
mentioning
confidence: 99%